Tissue multicolor STED nanoscopy of presynaptic proteins in the calyx of Held - Kempf, Christian; Staudt, Thorsten M.; Bingen, Pit; Horstmann, Heinz; Engelhardt, Johann; Hell, Stefan; Kuner, Thomas (PLOS ONE, 2013)
The calyx of Held, a large glutamatergic terminal in the mammalian auditory brainstem has been extensively employed to study presynaptic structure and function in the central nervous system. Nevertheless, the nanoarchitecture of presynaptic proteins and subcellular components in the calyx terminal and its relation to functional properties of synaptic transmission is only poorly understood. Here, we use stimulated emission depletion (STED) nanoscopy of calyces in thin sections of aldehyde-fixed rat brain tissue to visualize immuno-labeled synaptic proteins including VGluT1, synaptophysin, Rab3A and synapsin with a lateral resolution of approximately 40 nm. Excitation multiplexing of suitable fluorescent dyes deciphered the spatial arrangement of the presynaptic phospho-protein synapsin relative to synaptic vesicles labeled with anti-VGluT1. Both predominantly occupied the same focal volume, yet may exist in exclusive domains containing either VGluT1 or synapsin immunoreactivity. While the latter have been observed with diffraction-limited fluorescence microscopy, STED microscopy for the first time revealed VGluT1-positive domains lacking synapsins. This observation supports the hypothesis that molecularly and structurally distinct synaptic vesicle pools operate in presynaptic nerve terminals.
Gesehen am 23.04.2021